The Influence of the Human Development Index and Gini Ratio on the Poverty Level in West Java Province - Fibriani, Mega; Huda, Nurul (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to "analyze the effect of Human Development Index and Gini Ratio on poverty rate". The sample of this study is 27 districts/cities in West Java with data for 10 years (2015-2024). The analysis method of this study is panel data regression analysis. The results showed that "the Human Development Index and Gini Ratio had a significant effect on the poverty rate". This research provides a perspective that measuring the IPM and Gini Ratio can provide a new perspective in determining policies for the community. As a practical contribution, the government can optimize policies to improve people's welfare, such as enhancing the quality of education, healthcare, and income distribution. This can reduce social and economic problems and periodically increase human development so that the growth of the poverty rate can be reduced.